The State, Popular Mobilisation and Gold Mining in Mongolia Shaping 'Neoliberal' Policies - Bumochir, Dulam (Economic Exposures in Asia, 2020)
Mongolia's mining sector, along with its environmental and social costs, have been the subject of prolonged and heated debate. This debate has often cast the country as either a victim of the 'resource curse' or guilty of 'resource nationalism'. In The State, Popular Mobilisation and Gold Mining in Mongolia, Dulam Bumochir aims to avoid the pitfalls of this debate by adopting an alternative theoretical approach. He focuses on the indigenous representations of nature, environment, economy, state and sovereignty that have triggered nationalist and statist responses to the mining boom. In doing so, he explores the ways in which these responses have shaped the apparently 'neo-liberal' policies of twenty-first century Mongolia, and the economy that has emerged from them, in the face of competing mining companies, protest movements, international donor organizations, economic downturn, and local and central government policies.